A TAD Skeptic: Is 3D Genome Topology Conserved?. Issue 3 (March 2021) - Eres, Ittai E.; Gilad, Yoav
Abstract : The notion that topologically associating domains (TADs) are highly conserved across species is prevalent in the field of 3D genomics. However, what exactly is meant by 'highly conserved' and what are the actual comparative data that support this notion? To address these questions, we performed a historical review of the relevant literature and retraced numerous citation chains to reveal the primary data that were used as the basis for the widely accepted conclusion that TADs are highly conserved across evolution. A thorough review of the available evidence suggests the answer may be more complex than what is commonly presented. Highlights: Topologically associating domains (TADs) are highly self-interacting regions in the genome, identified through analysis of chromosome conformation capture data. TADs are often thought of as stable neighborhoods of gene regulation, constraining possible interactions between cis -regulatory elements and their target genes. TADs are poorly defined from a biological perspective and have low concordance across different inference algorithms. To date, comparative studies of TAD structures did not properly account for study design, technical, and analytical issues, but often concluded that TADs are highly conserved across species. A careful examination of the available interspecies comparative data to assess TAD conservation suggests that, while they certainly have some functional conservation, specific TAD structures and locations may not be especially conserved across evolutionary lineages.